ANALISIS TERHADAP PROGRAM PENDIDIKAN ANAK USIA DINI PADA RENCANA KERJA PEMERINTAH TAHUN 2009 - Wawan S Suherman; Endang Sulistyowati (LPMPP Universitas Negeri Yogyakarta, 2009)
This article analyzes the main program for Early Childhood Education (ECE) in the government program in 2009 stated in the President Regulation Number 38 Year 2008. The analysis employs the public policy model by Joko Wiyono, which is an applied analysis descriptive in nature, focusing on the content analysis. The targets are to analyze (1) the main determinant factors, (2) policy contents, and (3) expected and unexpected effects of the policy. The results of the analysis show that the determinant factors have not taken into account of the gap in the ECE implementation, concerns about the discontinuity among types of ECE services, and the development of the kindergarten education discourse. The contents of the program have not made ECE a priority, not all types of ECE services have been developed, and the coordinator of ECE programs has not been explicitly appointed. The objectives of the ECE programs have not set targets quantitatively. Keywords: public policy analysis, Early Childhood Education